Authoritarianism and Virtual Regionalism: The Gulf Cooperation Council during Arab Uprisings. Issue 2 (3rd April 2019) - Magued, Shaimaa
ABSTRACT: In spite of the inability of Gulf countries to develop a successful collective security strategy as asserted by the existing literature, the study contends that they have exceptionally adopted it toward their domestic uprisings. Based on the security regime theory, this study argues that threats of revolutionary sociopolitical change incentivize authoritarian regimes, such as Gulf countries, to formulate a collective security strategy within multilateral instances. By relying on a critical discourse analysis, the study traces Gulf countries' perception of the different uprisings as reported by different national newspapers from December 2010 till March 2018.